2018
DOI: 10.1111/all.13502
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of probiotic Lactobacillus rhamnosus GG prevents birch pollen‐induced allergic asthma in a murine model

Abstract: Intranasally administered L. rhamnosus GG prevents the development of cardinal features of birch pollen-induced allergic asthma in a strain-specific manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 39 publications
3
68
1
2
Order By: Relevance
“…Alternatively, the association between posthospitalization increases in Moraxella or Streptococcus species abundance and recurrent wheezing might be causal (ie, microbiota might influence host immune response to viral infection). 23,29,30 If true, influencing microbiome reassembly after hospitalization for bronchiolitis either with antibiotics 22,23 or, preferably, with intranasal administration of protective species 31 might be an approach to help prevent asthma in this high-risk group. This study has potential limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the association between posthospitalization increases in Moraxella or Streptococcus species abundance and recurrent wheezing might be causal (ie, microbiota might influence host immune response to viral infection). 23,29,30 If true, influencing microbiome reassembly after hospitalization for bronchiolitis either with antibiotics 22,23 or, preferably, with intranasal administration of protective species 31 might be an approach to help prevent asthma in this high-risk group. This study has potential limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic applications have been shown to impact effector and regulatory T‐cell responses in airway disease, resulting in the restoration of the Th1/Th2 immune balance, and/or stimulation of regulatory cytokine production and the regulatory T‐cell (Treg) subset . This typically leads to a reduction in lung Th2 inflammatory cytokine levels (eg, IL‐5 and IL‐13) and the attenuation of AHR, as recently demonstrated for preventive intranasal administration of L. rhamnosus GG in a mouse model of birch pollen–induced allergic asthma . Additional immunomodulatory properties of probiotics in airway disease, including the stimulation of mucosal IgA levels and allergen‐specific B‐ and T‐cell responses, are well described elsewhere …”
Section: Probiotic Interactions With the Immune Systemmentioning
confidence: 97%
“…The administration route of these probiotics is typically oral, via drinking water or food, or through intragastric intubation . More recently, intranasal administration of probiotic bacteria has been increasingly explored in different mice studies . In the study of Spacova et al, the authors demonstrated that intranasal administration of L. rhamnosus GG attenuated birch pollen–induced asthma in mice .…”
Section: Clinical Application Of Probiotics For the Airwaysmentioning
confidence: 99%
“…Intranasale Gabe von Lactobacillus rhamnosus führte zunächst zu einer vorübergehenden Kolonisierung in den oberen Luftwegen bei Mäusen und reduzierte präventiv die Symptome einer künstlich induzierten Birkenpollenallergie mit reduzierter bronchialer Hyperreaktivität. In der BAL fand man weniger Eosinophile und weniger IL-5 und IL-13 im Vergleich zu einer Kontrollgruppe (Spacova et al 2018).…”
Section: Im Vergleich Zu Placebo Single-probiotikum Kombinationsprobiunclassified